Government Low-Carbon Regulations Based on Supply Chain Members’ Behavior and Consumers’ Channel Preference in a Dual-Channel Supply Chain - Bingquan Liu; Xuran Chang; Boyang Nie; Yue Wang; Lingqi Meng (Complexity)
As carbon emissions are increasing due to the development of economy, low-carbon supply chain plays an important role in carbon emissions reduction and the dual-channel supply chain has become a hit because online shopping is developing rapidly. Therefore, this paper builds a Stackelberg game model led by the manufacturer in a dual-channel supply chain to examine the reaction of the government under centralized or decentralized decisions-making structures with different low-carbon strategies. The result shows that the government can achieve higher profits by taking incentive or punitive measures for centralized decision-making supply chain no matter they invest in emissions reduction or not. Moreover, for decentralized decision-making mode, increasing low-carbon subsidies for retailers can achieve a win-win result between the supply chain and the government; and, finally, channel competition is good for improving the supply chain and social benefits. Therefore, the government is responsible for taking reasonable subsidy policies, formulate industry’s low-carbon standards, and properly guide competition between supply chain members to achieve higher profits.